PRINCIPLES OF IMPROVEMENT OF HEAVY MIXTURES FROM COTTON RAW MATERIALS - IBROKHIMOV, ILGORBEK; KHUSANOV , SADI (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article provides an analysis of devices that capture heavy impurities from the composition of cotton raw materials available in cotton ginning enterprises and ways of their improvement. In addition, the condition of the equipment used in foreign enterprises was also analyzed for comparative studies. During the research, the negative effects of heavy compounds in cotton on the working organs of devices in the technological process were also studied.